The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.2214/ajr.11.7602
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of the Anterior Peritoneal Reflection at Rectal MRI

Abstract: The peritoneal reflection was identified on MRI by two radiologists in the majority of patients with rectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(56 citation statements)
references
References 11 publications
2
53
0
1
Order By: Relevance
“…have reported that this line can be identified in 74.4% of patients on MR imaging of the pelvis [1]. The tip of the seminal vesicles in men and the uterocervical angle in women were constant landmarks to determine the location of the most inferior point of the peritoneal membrane [1]. The reasons for difficulty in identifying the anterior peritoneal reflection line included postoperative status, poor image quality, motion artifact, a paucity of pelvic fat planes, retroversion of the uterus and presence of a large, exophytic rectosigmoid tumor [1].…”
Section: Mass Localizationmentioning
confidence: 92%
See 2 more Smart Citations
“…have reported that this line can be identified in 74.4% of patients on MR imaging of the pelvis [1]. The tip of the seminal vesicles in men and the uterocervical angle in women were constant landmarks to determine the location of the most inferior point of the peritoneal membrane [1]. The reasons for difficulty in identifying the anterior peritoneal reflection line included postoperative status, poor image quality, motion artifact, a paucity of pelvic fat planes, retroversion of the uterus and presence of a large, exophytic rectosigmoid tumor [1].…”
Section: Mass Localizationmentioning
confidence: 92%
“…Gollub and al. have reported that this line can be identified in 74.4% of patients on MR imaging of the pelvis [1]. The tip of the seminal vesicles in men and the uterocervical angle in women were constant landmarks to determine the location of the most inferior point of the peritoneal membrane [1].…”
Section: Mass Localizationmentioning
confidence: 98%
See 1 more Smart Citation
“…Identification of the anterior peritoneal reflection can be challenging and is best assessed on both axial and sagittal T2 images. In the mid- distance from the anorectal junction to the anterior peritoneal reflection, as measured in a straight line on a sagittal image was 6.7-6.9 cm in a published series [23]. Figure 6 shows examples of the anterior peritoneal reflection in the female and male pelvis on sagittal T2 images.…”
Section: Assessment Of the Anterior Peritoneal Reflectionmentioning
confidence: 93%
“…It offers several theoretical advantages over EUS as it reveals a larger field of view and permits the study of stenotic, nontraversable tumors [18,40,41]. Recently, the identification of the anterior peritoneal reflection on MRI in 74 % of patients in one study is important given the impact of this landmark on surgical planning [42]. A meta-analysis of 90 articles (1995-2002) compared the utility of MRI, radial EUS without FNA, and CT for staging with histopathology correlation as the gold standard and came to the following conclusions: For T1/T2 lesions, EUS and MRI had similar sensitivity, but specificity was higher in EUS (86 vs. 69 %); for T3 tumors, the sensitivity of EUS was significantly higher than that of MRI or CT [43].…”
Section: Mri Versus Eus Assessmentmentioning
confidence: 99%